Bioecological aspects of triatomines and marsupials as wild Trypanosoma cruzi reservoirs in urban, peri‐urban and rural areas in the Western Brazilian Amazon. Issue 3 (4th January 2021) - Magalhães, L.; Silveira, H.; Prestes, S.; Costa Magalhães, L. K.; Santana, R. A.; Ramasawmy, R.; Oliveira, J.; Roque, C. C. R.; Silva Junior, R. C. A.; Fé, N.; Duarte, R.; Maciel, M.; et al.
Abstract: In the Amazon region, Trypanosoma cruzi transmission cycles involve a great diversity of Triatominae vectors and mammal reservoirs. Some Rhodnius spp. mainly inhabit palm trees that act as microhabitats for hosts and vectors. The current study aimed to describe aspects of the bio‐ecology of the vectors and reservoirs of T. cruzi in relation to human populations resident near areas with large quantities of palm trees, in rural, peri‐urban and urban collection environments, located in the Western Brazilian Amazon. Rhodnius pictipes and Didelphis marsupialis were respectively the most predominant vector and reservoir, with rates of 71% for R. pictipes and 96.5% for D. marsupialis. The vast majority of T. cruzi isolates clustered with TcI. The most prevalent haplotype was TcI COII1 (69.7%). Mauritia flexuosa and Attalea phalerata were the main ecological indicators of infestation by triatomines. Birds were the most common food source (27, 71%). T. cruzi isolated from R. robustus has the haplotype HUM‐13, previously detected in a chronic Chagas patient living in the same area. Our results demonstrate the relevance of this study, with the occurrence of elevated infection rates in animals, and suggest the importance of the Amazon zones where there is a risk of infection in humans. Abstract : Four species of triatomine were detected: Rhodnius pictipes, Rhodnius robustus, Panstrongylus geniculatus and Eratyrus mucronatus ; the highest triatomine presence was observed in urban areas. Vector foods source: B ird was the most common food source and was collected on Attalea maripa palms, Attalea phalerata, Oenocarpus bacaba and Mauritia flexuosa . Sylvatic reservoirs: The highest infection rates were observed in D. marsupialis, which were collected in urban areas. The DTU identified was TCI.